PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION BERBANTUAN MEDIA CANVA TERHADAP PENINGKATAN HASIL BELAJAR IPAS - Nuri Nur Akmar; Jaka Permana; Sopyan Hendrayana (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to determine the effect of the cooperative learning model Student Teams Achievement Division (STAD) assisted by Canva media on students' learning outcomes in the Natural and Social Sciences (IPAS) subject, specifically on the topic "Plants as the Source of Life on Earth" in Grade IV of SDN Cibeber, West Bandung Regency. The background of this research is based on the low learning outcomes in IPAS, which are caused by the lack of variation in learning models and media used during the learning process, an unconducive classroom environment, and limited collaboration among peers. The research method used is a quantitative quasi-experimental method with a control group design. The sample of this study consisted of two classes totaling 56 students: Class IV A as the experimental class received treatment using the STAD cooperative learning model assisted by Canva media, while Class IV B as the control class used the Problem-Based Learning (PBL) model. The instruments used included both tests and non-test methods. The test instruments were in the form of pretests and posttests using multiple-choice questions, while the non-test instruments included observation, interviews, and documentation. The results showed a significant improvement in learning outcomes in the experimental class compared to the control class. Based on the results of the independent t-test, the significance value (2-tailed) was 0.001 < 0.05, indicating a significant difference between the posttest results of the two classes. Moreover, the effect size calculation result was 1.399, which falls into the "very large" category. This proves that the implementation of the STAD model assisted by Canva media has a positive and significant effect on improving IPAS learning outcomes for Grade IV A students at SDN Cibeber, West Bandung Regency.